2017
DOI: 10.1002/bdd.2088
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of dinalbuphine sebacate and nalbuphine in human after intramuscular injection of dinalbuphine sebacate in an extended‐release formulation

Abstract: Nalbuphine is a semi-synthetic opioid indicated for the relief of moderate to severe pain. Its short half-life requires frequent injections in clinical practice, resulting in a greater incidence of adverse events. A prodrug of nalbuphine has been developed, dinalbuphine sebacate (DNS), dissolved in a simple oil-based injectable formulation, which could deliver and maintain an effective blood level of nalbuphine. An open-label, prospective, two-period study was performed in healthy volunteers to verify the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“… 28 Tien et al previously demonstrated DNS as an extended-release nalbuphine that takes approximately 6 days to completely release into the bloodstream. 29 When released, DNS can be rapidly hydrolyzed to nalbuphine by esterase to exert its analgesic effect. Therefore, with a lower maximum blood concentration, DNS has a better safety profile than nalbuphine itself.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Tien et al previously demonstrated DNS as an extended-release nalbuphine that takes approximately 6 days to completely release into the bloodstream. 29 When released, DNS can be rapidly hydrolyzed to nalbuphine by esterase to exert its analgesic effect. Therefore, with a lower maximum blood concentration, DNS has a better safety profile than nalbuphine itself.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Our results showed that the two treatments had a similar safety profile; none of the patients treated with DS reported postoperative pruritus, even among those who received rescue morphine. Based on pharmacokinetics of DS, the relatively low concentration of nalbuphine provided a background analgesic effect 30 which might explain why patients in DS group required no supplemental analgesics after 24 hours, by contrast those in the postoperative morphine group.…”
Section: Discussionmentioning
confidence: 99%
“…Extended-release dinalbuphine sebacate (ERDS, Naldebain ® , Lumosa Therapeutics, Taipei, Taiwan) is a pro-drug of nalbuphine, which acts as a mixed kappa opioid agonist/mu opioid antagonist providing sufficient analgesia for moderate to severe pain after a single intramuscular administration. ERDS can rapidly hydrolyze to nalbuphine by esterases in the human bloodstream [ 10 ]. A randomized study has reported that pre-operative intramuscular administration of ERDS exhibits a well-tolerated safety profile and weekly analgesic effect, less post-operative analgesics use, and prolonged time to the first use of analgesics in patients undergoing hemorrhoidectomy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%